Legal Resource for School Health Services - Resha, Cheryl A.; Taliaferro, Vicki (SchoolNurse.com, 2017)
A reference regarding legal issues impacting school health. The book provides information on over 50 topics that school health services programs and school nurses encounter, addresses legal implications and presents legal resources and references that can be applied to practice and policy development. - Cover
Keywords: Law and legislation; School nursing; United States; dept.nur; faculty_collection